1993
DOI: 10.1042/cs0840651
|View full text |Cite
|
Sign up to set email alerts
|

Clenbuterol, a β-Adrenoceptor Agonist, Increases Relative Muscle Strength in Orthopaedic Patients

Abstract: 1. The sympathomimetic agent clenbuterol has a muscle-specific anabolic effect in normal and wasted muscles from animals. This trial was designed to examine the effect of the drug on the recovery of muscle strength and area after open medial meniscectomy. 2. A double-blind, completely randomized, placebo-controlled study was carried out on 20 healthy male patients. Muscle strength and cross-sectional area were determined before and after surgery. Patients were treated with drug or placebo for 4 weeks postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
94
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 11 publications
3
94
0
2
Order By: Relevance
“…Although the potential therapeutic role for clenbuterol in muscular dystrophy has received much attention (Maltin et al 1987(Maltin et al , 1993Martineau et al 1992;Zeman et al 1994;Hayes & Williams 1994;Dupont-Versteegden et al 1995), the majority of these studies have investigated only whether clenbuterol alters the mass and isometric force-producing capacity of isolated muscles. Whether clenbuterol affects the dynamic properties of dystrophic skeletal muscle has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Although the potential therapeutic role for clenbuterol in muscular dystrophy has received much attention (Maltin et al 1987(Maltin et al , 1993Martineau et al 1992;Zeman et al 1994;Hayes & Williams 1994;Dupont-Versteegden et al 1995), the majority of these studies have investigated only whether clenbuterol alters the mass and isometric force-producing capacity of isolated muscles. Whether clenbuterol affects the dynamic properties of dystrophic skeletal muscle has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that SMN is phosphorylated at serines 28 and (8,12,14). ␤-Adrenergic agonists have been shown to improve muscle strength in human subjects with healthy and diseased muscle (29)(30)(31), and daily albuterol treatment had beneficial effects in an open-label pilot study in SMA type II and III patients (16). Salbutamol has been also been shown to increase SMN protein levels in patient-derived fibroblasts (1).…”
Section: Discussionmentioning
confidence: 99%
“…Orthopedic patients administered 20 g clenbuterol twice daily for 4 wk did not exhibit any improvement in the absolute strength of their knee extensor muscles compared with patients given placebo (27). A 3-mo pilot trial of albuterol (16 mg/day) given to 15 patients with facioscapulohumeral muscular dystrophy led to improved maximum voluntary isometric contractile performance, and this was followed by a year-long randomized, double-blind, placebocontrolled trial where patients were treated with up to 16 mg of albuterol twice daily (20).…”
mentioning
confidence: 99%
“…The potential for ␤ 2 -agonists to improve the size and strength of muscles of human patients affected by neuromuscular diseases has received only limited attention (20,27). Orthopedic patients administered 20 g clenbuterol twice daily for 4 wk did not exhibit any improvement in the absolute strength of their knee extensor muscles compared with patients given placebo (27).…”
mentioning
confidence: 99%